Metode Pembelajaran Sastra Arab - Azkia Muharom Albantani (Alfaz (Arabic Literatures for Academic Zealots), 2018)
AbstractLiterature (al-Adab) is the delivery of something by the processing of deep feelings that are full of value and art about the image that will be given and expressed in a certain form with certain rules as well. Periodization of literature begins since the period of ignorance, the period of Islam which includes Daulah Umayyah, continued Abbasiyah period, Turki Usmani, and the last modern period. While the purpose of learning literature among them to increase knowledge and understanding of students to literature to life more directed and become good; also help students understand the social limps in their lives and at the same time how to play a role to overcome them.AbstrakSastra (al-Adab) adalah penyampaian sesuatu dengan pengolahan perasaan yang mendalam yang sarat nilai dan seni tentang gambaran yang akan diberikan dan diekspresikan dalam bentuk tertentu dengan kaidah-kaidah yang tertentu pula. Periodisasi sastra dimulai sejak periode jahiliyah, periode Islam yang didalamnya termasuk Daulah Umayyah, dilanjutkan periode Abbasiyah, Turki Usmani, dan terakhir periode modern. Sementara tujuan dari pembelajaran sastra di antaranya untuk menambah pengetahuan dan pemahaman siswa terhadap sastra hingga hidupnya lebih terarah dan menjadi baik; juga membantu siswa memahami kepincangan sosial dalam kehidupannya dan sekaligus cara memainkan peran untuk mengatasinya.